Control strategies for charging and discharging policies of rechargeable batteries - Chen, Can. (2011)
Rechargeable batteries will play a more and more important role in future. No matter from the performances or from the need for energy conservation and environment protection, Li-ion battery will become a leading candidate for the next generation rechargeable batteries. However, there are still many challenges in making full use of Li-ion battery. This thesis is focused on the challenge of the control strategies for charging and discharging policies of Li-ion battery. Firstly, to comparing the effects of different charging and discharging policies, a comprehensive Li-ion battery electrical model is proposed. It can be suitable to the time-varying working condition and it can provide accurate remain runtime and I-V performance predictions. Secondly, several promising charging policies including CV-CC-CV, Multistep-CC-CV and Pulse policies are tested and compared with each other. Each policy has its own advantages and disadvantages, so that they should be chosen as the implementation situations. Thirdly, the pulse discharging policy is regarded as the emphasis of the discharging part. Due to the drawbacks of the electrical model, pulse discharging policy can't be simulated directly. As a result, it is just presented in theory. Fourthly, owing to the necessary of the equalizing policies in the charging and discharging processes, the traditional equalizing policies are represented. In addition, a flexible equalizing circuit topology is proposed. It can achieve a good equalizing effect with short time. However, it may need a complex control strategy to support. Consequently, its priorities are analyzed theoretically, too. Lastly, the fuzzy control strategy is treated as the whole control strategy. With it, the charging and equalizing processes regarded as a representative are simulated simultaneously. The simulation results show out the excellent control effect of the strategy. Then, the conclusion of this report and the recommendations for future work are given.